ANALISIS INTERAKSI SOSIAL SISWA-SISWI KELAS AKSELERASI (STUDI DI SMA NEGERI 1 DENPASAR BALI) - Bina Meni, Gregorius Yakobus; Zuryani, Nazrina; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT Grade acceleration is an acceleration program which provides services accelerated program needs students who have special characteristics in terms of intellectual potential and special talent to be served according to their needs. In the expansion there are some negative impacts contained in the accelerated program for gifted children, the negative impact of the accelerated program that is located on the problems of social adjustment, where the problem is the accelerated program students are encouraged to do well academically, this will reduce the time to perform other activities. The problems in the review in this study are as follows. (1) How is the acceleration of social interaction in the classroom? (2) How The social interaction between students accelerated classes and regular classes? The approach used in this research is descriptive qualitative done in SMAN 1 Denpasar. The theoretical basis used in the study of social interaction and disiosiatif according associative and Gillin Gillin. The results of this study found that the social interaction that is not going well in class acceleration and accelerated classes with regular classes, interaction that is not going well is causing gaps and chasms that separation between the other student with other students in accelerated classes. Keywords: grade acceleration, interaction associative, dissociative interaction.